KETERLIBATAN WOODSIDE PETROLEUM ENERGY AUSTRALIA DALAM PENGELOLAAN MINYAK DAN GAS DI CELAH TIMOR - Stary Kendly; Idjang " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the involvement of Australian oil companies in oil and gas management in the Timor Gap. Timor Leste has been listed as one of the world's independent nations on 20 May 2002. Australia became an active country in East Timor's independence during the reign of Prime Minister of Australia, Jhon Howard. Timor Leste is a country with natural resources, oil and gas in the Timor Gap that can improve and develop the economy in Timor Leste. This study uses the theory of comparative advantage which sees that as an independent country, Timor Leste specializes in the production of the country's oil and gas fields in Timor-Leste that attract the attention of other countries to get involved and cooperation in oil and gas management in the Timor Gap. Level of analysis and level of analysis used in this study is double. At the level of analysis nation state and multinational companies. The method used is qualitative and data collection through library research. This access to energy is an important driver of Australia to be involved in handling the turmoil in East Timor following the referendum. Australian companies are involved in oil and gas management in the Timor Gap. This can be seen from Australian oil companies operating in each of the oil and gas fields in the Timor Gap. Australia and Timor Leste recognize the importance of oil on the seabed for the future of Timor-Leste so that oil company contracts are maintained and exploration in the Timor Sea is continued to allow Timor-Leste to receive revenues from the oil and gas. Keywords : Australia, Timor Gap, Timor Leste, Multinational Coorperation, Woodside Petroleum Energy, Oil and Gas